A Hybrid Audio Steganography Method - Acharjee, T; Choudhury, A; Kumar, P (International Journal of Computer Sciences and Engineering, 2018)
In this era of smartphones and gadgets assisted by high speed internet connectivity, the volume of data transmission and storage have gained a lot. As a result data security and confidentiality has become more important issue than ever. Steganography is one data hiding technique which helps to send some secret message to the receiver by concealing it in a cover file. In this paper, we have focused on the Audio Steganography method. The major challenge in audio steganography is to obtain robust high capacity steganographic systems. This paper presents a secure data transfer technique using Audio Steganography. Here we have proposed a hybrid method combining modified Least Significant Bit (LSB) and spread spectrum based audio steganography methods. We have implemented the proposed method and compared the results with the other methods using two quality measurement techniques, namely, Peak signal to noise ratio (PSNR) and Mean Square Error (MSE).